Anisotropic magnetoresistance: materials, models and applications - Ritzinger, Philipp; Výborný, Karel (Royal Society open science, 2023)
Resistance of certain (conductive and otherwise isotropic) ferromagnets turns out to exhibit anisotropy with respect to the direction of magnetization: R∥ for magnetization parallel to the electric current direction is different from R⊥ for magnetization perpendicular to the electric current direction. In this review, this century-old phenomenon is reviewed both from the perspective of materials and physical mechanisms involved. More recently, this effect has also been identified and studied in antiferromagnets. To date, sensors based on the anisotropic magnetoresistance (AMR) effect are widely used in different fields, such as the automotive industry, aerospace or in biomedical imaging.
Keywords: resistance; transition metals; ferromagnets; antiferromagnets; anisotropic magnetoresistance; sensors